Functional Profiling of CFTR-Directed Therapeutics Using Pediatric Patient-Derived Nasal Epithelial Cell Models - Park, Jeffrey KiHyun; Shrivastava, Anura; Zhang, Chengkang; Pollok, Brian A.; Finkbeiner, Walter E.; Gibb, Elizabeth R.; Ly, Ngoc P.; Illek, Beate (Frontiers in Pediatrics, 2020)
Cells derived from patients with cystic fibrosis (CF) can support personalized medicine by providing 2-dimensional (2-D) cell culture models for ex vivo CFTR functional assays. Here, we created nasal epithelial cell cultures from CF patients with uncommon CFTR mutations to characterize CFTR chloride transport function in the following CF genotypes: F508del/R117H(7T), R334W/4061-G>A, F508del/c.850dupA, F508del/F508del, and CFTRdele2,3(21kb)/CFTRdele2,3(21kb). Cells were collected from pediatric CF patients between the age of 3 years to 20 years at the UCSF Benioff Children’s Hospital Oakland, expanded by the EpiXTM technology and grown as differentiated 2-D layers using air-liquid interface (ALI) conditions. The standard Ussing chamber assay was used for real-time measurement of transepithelial chloride ion transport and assessment of CFTR-directed therapeutics. Quantitative analysis of short-circuit current reveals that F508del/R117H(7T) retains 56% of wildtype CFTR function after stimulation by forskolin and VX-770, R334W/406-1G>A retains 24%, F508del/c.850dupA retains 12%, F508del/F508del retains 12%, and CFTRdele2,3(21kb)/CFTRdele2,3(21kb) retains 9%. Among the CFTR modulators considered in this study, CFTR function is rescued better by VX-770+VX-809 for F508del/R117H(7T), R334W/406-1G>A, F508del/c.850dupA, and F508del/F508del; and VX-770+VX-661 was more efficient for CFTRdele2,3(21kb)/CFTRdele2,3(21kb). In addition to characterizing the electrophysiological profile of mutant CFTR activity in native tissue for five CF genotypes, our study also exemplifies the promising paradigm of bed-to-benchside cooperation and personalized medicine.